Evidence for a polariton-mediated biexciton transition in single-walled carbon nanotubes - Lüttgens, Jan; Kuang, Zhuoran; Zorn, Nicolas; Buckup, Tiago; Zaumseil, Jana (ACS photonics, 2022)
Strong coupling of excitonic resonances with a cavity gives rise to exciton-polaritons which possess a modified energy landscape compared to the uncoupled emitter. However, due to the femtosecond lifetime of the so-called bright polariton states and transient changes of the cavity reflectivity under excitation, it is challenging to directly measure the polariton excited state dynamics. Here, near-infrared pump-probe spectroscopy is used to investigate the ultrafast dynamics of exciton-polaritons based on strongly coupled (6,5) single-walled carbon nanotubes in metal-clad microcavities. We present a protocol for fitting the reflectivity-associated response of the cavity using genetic algorithm-assisted transfer-matrix simulations. With this approach, we are able to identify an absorptive exciton-polariton feature in the transient transmission data. This feature appears instantaneously under resonant excitation of the upper polariton but is delayed for off-resonant excitation. The observed transition energy and detuning dependence point toward a direct upper polariton-to-biexciton transition. Our results provide direct evidence for exciton-polariton intrinsic transitions beyond the bright polariton lifetime in strongly coupled microcavities.